Sistem Pendukung Keputusan Penentuan Anggaran Keuangan menggunakan Metode Wp (Weighted Product) Pada Panti Wreda Griya Nugraha Bandar Lampung - Rosyana Fitria Purnomo; Fatimah Fahurian (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2023)
Decision Support Systems are part of computer-based information systems that are used to support decision making in an organization or company. One type of decision making method is WP (Weighted Product). This research aims to implement a Decision Making System using the WP (Weighted Product) method on the financial budget in one of the Nursing Homes, which is beneficial for stakeholders in the nursing home so that there are no errors in decision making in determining the financial budget at the Griya Nugraha Nursing Home. The assessment criteria include the number of needs, number of elderly people, time period, and savings funds. The information system was built on a desktop basis with a system management database using SQL. From the test results of the decision support system for determining the financial budget which was tried using 10 samples of nursing home residents which produced the best score of 0.1035 where the assessment was between 0-1, and the maximum score was 1. This research can help in representing decisions that are usually issued by the Chairman. In general, every time you do a financial budget at a nursing home.